Od niesprawiedliwości społecznej po sprawiedliwość epistemiczną – polski dramat posttraumatyczny - Baluch, Wojciech (Przestrzenie Teorii, 2024)
The article unfolds the history of Polish drama from the traumatic moment of transition that began in Poland in 1989 to the present. The methodological framework of the argument is set by the concepts of post-traumatic growth and epistemic injustice. The first concept allows at the beginning of the article to look at the gap between the aesthetics of the dramas of the 1990s and the difficult experience of the Poles of the ongoing political transition. Epistemic injustice, on the other hand, which consists in the lack of a language to describe one’s own experience by less privileged groups, is a point of reference for the latest achievements of drama, which, through the inclusion of a wider range of co-creators in the creative process, develops languages that allow us to address issues that we have not had access to before. The whole history of overcoming the traumatic exclusions experienced by Polish society since the transition has been shown on the example of selected dramatic works, which, finding at the beginning of the 21st century a language adequate to express the experiences of the people of that time, in the long run, increasingly broadens its horizon, thanks to the development of new drama.